Assessment of the cultural significance of built heritage in Zamboanga City and their appropriate conservation approach - Aquino, Loretta May.; Orendain, Dan Jezreel (2016)
Zamboanga City has an extremely rich culture, combining the memories of the past with the present, and the culture of different peoples and religions. This translates well into much of their architecture and the conservation of which can provide future generations an insight into the colorful past of Zamboanga City. This study then is a comprehensive analysis of several heritage sites, or built heritages, within the City of Zamboanga. Specifically, these built heritages are Fort Pilar, the College of Education Building of the Western Mindanao State University , the Zamboanga City Hall, Plaza Pershing, the main branch of the Bank of the Philippine Islands in Zamboanga City, the Zamboanga East Central School, and lastly the Zamboanga Convention Center. According to the Burra Charter, there are different aspects of cultural significance, these being: Aesthetic aspect, Architectural aspect, Historical aspect, Scientific aspect and Social aspect. The cultural significance of each structure is assessed using a Significance Indicator Survey based on the Burra Charter?s definition of cultural significance. With this, the level of significance of each built heritage built is determined, whether each structure has an exceptional significance , considerable significance, some significance, little or no significance, or if it is intrusive. The level of significance of each built heritage is used to determine their appropriate conservation approach. This range from preservation, restoration, reconstruction, and adaptation.
Thesis (BS Architecture) -- University of the Philippines Mindanao, June 2016.